Efficacy and safety of neoadjuvant PD-1 inhibitors or PD-L1 inhibitors for muscle invasive bladder cancer: a systematic review and meta-analysis - Huang, Shibo; Huang, Yanping; Li, Chunyan; Liang, Yiwen; Huang, Miaoyan; Luo, Raoshan; Liang, Weiming (Frontiers in Immunology, 2024)
This meta-analysis aims to evaluate the efficacy and safety of neoadjuvant PD-1 inhibitors or PD-L1 inhibitors[PD-(L)1 inhibitors] for muscle-invasive bladder carcinoma(MIBC).Four databases (Medline, Embase, Web of Science and21 CENTRAL) were searched for articles studying neoadjuvant PD-(L)1 inhibitors for MIBC. The search time period was from the establishment of each database to July 21, 2023. Meta-analyses of pCR, pPR, Grade≥ 3 irAEs rate, RFS and OS were performed. 1 Shibo Huang and Yanping Huang contributed equally to this study. Results In total, twenty-two studies were included for meta-analysis. The overall pooled pCR of neoadjuvant PD-(L)1 inhibitors was 0.36(95%CI=0.30 0.42, P=0.00). In subgroup meta-analysis,the pooled PCR of PD-(L)1 inhibitors alone, PD-(L)1 inhibitors plus other ICI and PD-(L)1 inhibitors plus chemotherapy was 0.27(95%CI=0.19 0.35, P=0.1), 0.41(95%CI=0.21 0.62, P=0.01), 0.43 (95%CI=0.35 0.50, P=0.06), respectively. The overall pooled pPR of neoadjuvant PD-(L)1 inhibitors was 0.53(95%CI=0.46 0.60, P=0.00). In subgroup meta-analysis, the pooled pPR of PD-(L)1 inhibitors alone, PD-(L)1 inhibitors plus other ICI and PD-(L)1 inhibitors plus chemotherapy was 0.36(95%CI=0.22 0.51, P=0.01), 0.51(95%CI=0.39 0.62, P=0.43) and 0.61(95%CI=0.53 0.69, P=0.01), respectively. Kaplan-Meier curves for OS and RFS were reconstructed, but there was no significant difference among three groups in terms of OS or RFS. The pooled result of Grade≥ 3 irAEs rate for neoadjuvant PD-(L)1 inhibitors was 0.15(95%CI=0.09 0.22, P=0.00%). In subgroup analysis, the pooled result of Grade≥ 3 irAEs rate for PD-(L)1 inhibitors alone, PD-(L)1 inhibitors plus other ICI and PD-(L)1 inhibitors plus chemotherapy was 0.07(95%CI=0.04 0.11, P=0.84),0.31(95%CI=0.16 0.47, P=0.06) and 0.17(95%CI=0.06 0.31, I 2 =71.27%, P=0.01), respectively. Conclusions Neoadjuvant PD-(L)1 inhibitors were feasible and safe for muscle invasive bladder cancer. Compared with PD-(L)1 inhibitors alone,PD-(L)1 inhibitors plus other ICI and PD-(L)1 inhibitors plus chemotherapy were associated with higher pCR and pPR, but higher Grade≥3 irAEs.Kaplan-Meier curves for OS and RFS indicated that neoadjuvant PD-(L)1 inhibitors had an acceptable long-term prognostic, but it was not possible to discern statistical differences between the three neoadjuvant subgroups.